Pedagogical attention strategies in students with visual impairment - Rodríguez Noriega, Arnoldo Rafael; González Roys, Gustavo Adolfo; Martínez Arredondo, Leonardo Enrique (Revista UNIMAR, 2023)
The objective of this research was to understand the importance of pedagogical attention strategies in the classroom, for students with visual disabilities in the context of educational inclusion at the Universidad Popular del Cesar, Sabanas campus, Valledupar municipality. It was based on various authors and was developed under the qualitative approach in the phenomenological method. A documentary review and interviews were carried out with two students with visual disabilities and two teachers of the institution, where the important effort of the latter was evidenced when considering all their students in the pedagogical practice, including those with visual disabilities. It is concluded that there is a need to train teaching staff to work competently to achieve more important achievements in terms of educational inclusion and pedagogy of inclusion related to disability.